The immune receptors TLR4 and SLAMF1 regulate TNF release by human metapneumovirus in human macrophages - Sæterhaug Bye, Katja; Rian, Kristin; Ryan, Liv; Espevik, Terje; Anthonsen, Marit W.; Yurchenko, Maria (Frontiers in Immunology, 2025)
BackgroundHuman metapneumovirus (HMPV) is a major cause of acute respiratory disease in children, the elderly, and immunocompromised individuals. While pro-inflammatory cytokines and type I interferons (IFNs) are important for antiviral defense, excessive tumor necrosis factor (TNF) is associated with severe disease in HMPV and other respiratory infections. Hence, defining regulatory mechanisms by which HMPV induces TNF and IFN-β is important for therapeutic strategies in airway disease. The immunoregulatory receptors Toll-like receptor (TLR)4 and signaling lymphocytic activation molecule family 1 (SLAMF1) mediate TNF and IFN-β expression in response to LPS and Gram-negative bacteria, but their involvement in HMPV-stimulated cytokine expression is unclear.MethodsWe investigated the kinetics of TNF and IFNB1 expression in human monocyte-derived macrophages (MDMs) and THP-1 macrophage-like cells. The impact of SLAMF1 and TLR4 on TNF, IFNB1, and p38 MAPK was determined after their overexpression or knockout in THP-1 cells or silencing in MDMs.ResultsTLR4 knockout reduced TNF but not IFNB1 induced by HMPV, whereas SLAMF1 silencing reduced both cytokines. Overexpression of TLR4 or SLAMF1 enhanced p38 MAPK activation and TNF secretion, while silencing of TLR4 or SLAMF1 reduced p38 MAPK activation and TNF secretion. Pharmacological inhibition of p38 MAPK reduced both TNF and IFNB1, confirming its essential role in cytokine induction.ConclusionsTogether, our findings identify TLR4 and SLAMF1 as key regulators of early HMPV-induced inflammation via p38 MAPK. SLAMF1 additionally influences IFN-β responses and appears to affect viral replication dynamics. These insights suggest that targeting SLAMF1–TLR4 signaling may offer a therapeutic strategy to limit TNF-driven pathology in HMPV infection.